2018
DOI: 10.7717/peerj.4965
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, host-specificity and stability of sponge-associated fungal communities of co-occurring sponges

Abstract: Fungi play a critical role in a range of ecosystems; however, their interactions and functions in marine hosts, and particular sponges, is poorly understood. Here we assess the fungal community composition of three co-occurring sponges (Cymbastela concentrica, Scopalina sp., Tedania anhelans) and the surrounding seawater over two time points to help elucidate host-specificity, stability and potential core members, which may shed light into the ecological function of fungi in sponges. The results showed that IT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 101 publications
(184 reference statements)
3
38
1
Order By: Relevance
“…Sponges host a diverse bacterial microbiome and among high-microbial-abundance sponges such as those discussed in this study, the microbial population can comprise up to 35% weight of the sponge [3,4]. In addition to bacteria, sponges also host eukaryotic partners such as fungi and dinoflagellates [5]. Thus, from a molecular perspective, sponges can be conceptualized as a community of multiple interacting partners, referred to here as holobionts.…”
Section: Introductionmentioning
confidence: 99%
“…Sponges host a diverse bacterial microbiome and among high-microbial-abundance sponges such as those discussed in this study, the microbial population can comprise up to 35% weight of the sponge [3,4]. In addition to bacteria, sponges also host eukaryotic partners such as fungi and dinoflagellates [5]. Thus, from a molecular perspective, sponges can be conceptualized as a community of multiple interacting partners, referred to here as holobionts.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that these fungi have an important role to breakdown the complex nutrient from the environment. This idea is supported by Nguyen and Thomas (2018) who suggested that Fusarium and Cladosporium as a saprophyte could contribute to nutrient uptake by breakdown of the plant-derived detritus or other plankton from water. In addition, regarding the symbiotic interaction between the microbes and the host sponge, it can be also suspected that the prospective fungi produce extracellular enzymes to help the host sponge to breakdown the roots so that the sponge is able to spread and expand the colony.…”
Section: Discussionmentioning
confidence: 85%
“…Fifteen OTUs could not be classified either at the phylum or class level. Ascomycota and Basidiomycota divisions are widely distributed in marine sponges with Ascomycota being the dominant one [ 59 ]. Members of Sordariomycetes, Malasseziomycetes and Agaricomycetes were previously reported from specimens of Scopalina collected in Australia [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ascomycota and Basidiomycota divisions are widely distributed in marine sponges with Ascomycota being the dominant one [ 59 ]. Members of Sordariomycetes, Malasseziomycetes and Agaricomycetes were previously reported from specimens of Scopalina collected in Australia [ 59 ]. The very low number of fungal reads in comparison to the number of non-targeted DNA is in line with previous studies examining fungal communities in marine sponges by cultivation-independent methods [ 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation